Potential Analysis of Zakat in Sharia Banking For Alleviating Poverty - Anwar, Deky; Juniawati, Mutmainah; Muwazir, Mohd Rizal (Universitas Islam Negeri Raden Intan Lampung, 2023)
Zakat collection is considered as one of the economic instruments in Indonesia, particularly for the Muslim community, aimed at alleviating poverty. It is well-known that Indonesia has the largest Muslim population in the world, thus the potential of zakat for poverty alleviation in the country is significant. This research aims to analyze the extent of zakat potential in Islamic banking in Indonesia for poverty alleviation. The research utilizes a qualitative descriptive method with content analysis as the data analysis technique. Secondary data, specifically the annual reports of Islamic Commercial Banks (ICBs) from 2019 to 2021, serve as the documents for this study. The findings indicate that the potential of zakat in Islamic banking remains small compared to the potential that should exist in Indonesia. Therefore, it is advisable for the government to implement policies that focus on improving both the collection and management of zakat, involving both the public and the Islamic banking sector.